CuCr50 alloy and preparation method thereof
By optimizing the preparation method of CuCr50 alloy, including ball mill mixing, pre-pressing forming, gradient heating sintering and thermal isostatic pressure treatment, the problems of insufficient binding force, high initial investment and large mass fluctuations in the existing copper-chromium alloy preparation methods are solved, and the performance and reliability of the vacuum circuit breaker cut capacitance group are significantly improved.
Patent Information
- Application Number
- CN202411547932.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-28
AI Technical Summary
The existing copper-chromium alloy preparation methods have problems such as insufficient binding force, high initial investment and large quality fluctuations, which affect the performance and reliability of the vacuum circuit breaker capacitor group.
The optimized CuCr50 alloy preparation method is adopted, including ball mill mixing, pre-pressing molding, gradient heating sintering and hot isostatic pressure treatment, and the ratio of copper powder, chromium powder, conductive additives and reinforced phases is adjusted.
It significantly improves the conductivity, mechanical properties and density of CuCr50 alloy, enhances the resistance to welding and wear resistance, thereby improving the performance and reliability of the vacuum circuit breaker capacitor group and extending the service life of the contacts.
Smart Images

Figure CN119530581A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a CuCr 50 Alloy and method for preparing the same. Background Art
[0002] Copper-chromium alloy has good comprehensive properties, such as strong short-circuit current breaking capacity, high dielectric strength, ablation resistance, low current cutoff, etc. Since the air absorption effect of CuCr is greater than the degassing effect, it has better dynamic vacuum degree than other materials, so it is widely used in vacuum interrupters, etc.
[0003] At present, the methods for preparing copper-chromium alloy mainly include mixed powder sintering method, vacuum melting and casting method and arc melting method. Among them, the mixed powder sintering method is to mix copper and chromium powders and then sinter them, but because this method adopts solid phase sintering, the bonding force between product particles is relatively weak, which will affect the mechanical stability of long-term use; the vacuum melting and casting method heats the copper-chromium alloy to a temperature above the melting point in a vacuum to completely melt the copper-chromium alloy, and then casts it into shape, but this method requires a special vacuum environment and complex melting equipment, resulting in relatively high initial investment and operating costs; the arc melting method melts the copper-chromium raw materials by utilizing the high temperature generated by the electric arc, and forms the desired shape by rapid cooling, but this method has strict control over the chemical composition, temperature field and solidification rate in the molten pool, and is prone to unexpected quality fluctuations. Summary of the invention
[0004] The main purpose of this application is to provide a CuCr 50 The present invention aims to overcome the above-mentioned shortcomings of the prior art and provide a copper-chromium alloy contact that can improve the performance of cutting capacitor groups of vacuum circuit breakers.
[0005] To achieve the above objectives, this application provides the following technical solutions:
[0006] A CuCr 50 The alloy preparation method comprises: mixing copper powder, chromium powder, conductive additive and strengthening phase according to a preset ratio and then ball milling to obtain CuCr 50 Alloy powder; the CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 Alloy green body; the CuCr 50 The alloy green body is solid phase sintered to obtain CuCr 50 Alloy sintered body; the CuCr 50 The alloy sintered body is hot isostatically pressed to obtain CuCr 50 alloy.
[0007] Optionally, the conductive additive includes any one of the following: carbon black, graphite, carbon nanotubes and carbon fibers. The reinforcing phase includes carbide or oxide powder, wherein the carbide includes any one of the following: chromium carbide, tungsten carbide, titanium carbide and vanadium carbide; the oxide includes any one of the following: aluminum oxide, zirconium oxide and yttrium oxide.
[0008] Optionally, the sintering aid includes a boride or a silicide, wherein the boride includes any of the following: titanium boride or zirconium boride; the silicide includes any of the following: iron silicide, nickel silicide, cobalt silicide, molybdenum silicide, titanium silicide, zirconium silicide and tungsten silicide.
[0009] Optionally, in the CuCr 50 During the pre-pressing process of the alloy powder, the pressure is set to 9.5-12 MPa.
[0010] Optionally, in the CuCr 50 During the pre-pressing process of the alloy powder, the holding time is set to 0.1 to 0.3 s.
[0011] Optionally, the CuCr 50 The alloy green body is solid phase sintered.
[0012] Optionally, the CuCr 50 The sintering temperature of the alloy green body for solid phase sintering is 980-1070°C.
[0013] Optionally, the CuCr 50 The alloy sintered body is hot isostatically pressed at a temperature of 920 to 980°C.
[0014] Optionally, the CuCr 50 The alloy sintered body is hot isostatically pressed at a pressure of 110 to 140 MPa.
[0015] Optionally, the CuCr 50 The holding time of hot isostatic pressing of the alloy sintered body is set to 3 to 6 hours.
[0016] In addition, the present application also provides a CuCr 50 Alloy, the CuCr 50 The composition of the alloy and the mass percentage of each component are:
[0017] Chromium powder: 49.6~49.8%
[0018] Conductive additive: 0.01~0.03%
[0019] Strengthening phase: 0.2~0.7%
[0020] Copper powder: balance.
[0021] In addition, the present application also provides a contact, which is used in a vacuum interrupter. The contact is based on the CuCr 50 Alloy preparation.
[0022] Compared with the prior art, the present invention can bring the following technical effects: the present invention optimizes the ratio of copper powder, chromium powder, conductive additive and reinforcing phase, and adopts processes such as ball milling, pre-pressing, gradient temperature rise sintering and hot isostatic pressing to prepare high-performance CuCr 50 Alloy contact. This application can significantly improve the CuCr 50 The alloy's electrical conductivity, mechanical properties and density enhance its resistance to welding and wear, thereby greatly improving the performance and reliability of the vacuum circuit breaker capacitor bank and extending the service life of the contacts. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A CuCr 50 A schematic diagram of a process for preparing the alloy;
[0024] Figure 2 Another embodiment of the present invention provides a CuCr with a size of 50 μm. 50 Schematic diagram of the microstructure of the alloy after sintering;
[0025] Figure 3 Another embodiment of the present invention provides a CuCr having a size of 100 μm. 50 Schematic diagram of the microstructure of the alloy after sintering;
[0026] Figure 4 Another embodiment of the present invention provides a CuCr with a size of 50 μm. 50 Schematic diagram of the microstructure morphology of the alloy after hot isostatic pressing;
[0027] Figure 5 Another embodiment of the present invention provides a CuCr having a size of 100 μm. 50 Schematic diagram of the microstructure morphology of the alloy after hot isostatic pressing;
[0028] Figure 6 Another embodiment of the present invention provides a CuCr having a size of 100 μm. 50 Schematic diagram of the fracture microstructure of the alloy after hot isostatic pressing;
[0029] Figure 7 Another embodiment of the present invention provides a CuCr with a size of 200 μm. 50 Schematic diagram of the fracture microstructure of the alloy after hot isostatic pressing;
[0030] Figure 8It is CuCr provided by another embodiment of the present application 50 Schematic diagram of the macroscopic morphology of the alloy surface after laser treatment;
[0031] Fig. 9 It is CuCr provided by another embodiment of the present application 50 Schematic diagram of the microstructure morphology of the alloy surface after laser treatment. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0034] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0035] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0036] Figure 1A CuCr according to an embodiment of the present application 50 A schematic diagram of the process for preparing the alloy, such as Figure 1 As shown, the method includes:
[0037] S1: Copper powder, chromium powder, carbon black and tungsten carbide (WC) were mixed in a ratio of 50.09%, 49.7%, 0.01% and 0.2% and ball milled in a ball mill mixing tank for 8 hours with a ball-to-material ratio of 1:1 to obtain CuCr 50 alloy powder;
[0038] S2: The CuCr 50 The alloy powder is placed in a mold coated with a release agent, and the CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 The alloy green body, wherein the press pressure is set to 9.5 MPa, the holding time is set to 0.1 s, and the press pressure relief time is set to 1 s;
[0039] In this step, a release agent is applied to the inner wall of the mold cavity to facilitate demoulding and effectively prevent the mold from being damaged during the extrusion demoulding process. 50 When the alloy powder is placed in the mold coated with a release agent, the vibration frequency of the core rod should be controlled to about 10 to 15 times to ensure that the CuCr 50 The alloy powder is uniform in all parts of the mold cavity, so that high-quality CuCr can be obtained in subsequent processes. 50 If the number of vibrations of the mandrel is too small (i.e. less than 10 times), CuCr 50 The distribution of alloy powder in the mold is not uniform. If CuCr 50 If the alloy powder is not evenly distributed, it will affect the CuCr 50 The density and shape of the alloy green body will reduce the quality of the final contact material. In addition, if the core rod is vibrated too many times (i.e. more than 15 times), it will waste time and energy, and may cause unnecessary wear on the mold and core rod, thereby increasing production costs. Therefore, the number of core rod vibrations is controlled to 10 to 15 times, which is the result of practical experience of this application. The number of core rod vibrations is controlled to 10 to 15 times, which can ensure the quality of CuCr 50 The alloy powder is evenly distributed in the mold, which is conducive to obtaining CuCr with high density and regular shape. 50 Alloy green body, to lay a solid foundation for the subsequent sintering and hot isostatic pressing steps.
[0040] S3: The CuCr 50The alloy green body is placed in a vacuum sintering furnace and sintered by gradient heating to obtain CuCr 50 Alloy sintered body;
[0041] In this step, CuCr 50 Before the sintering of the alloy green body begins, the sintering furnace must first be evacuated to remove the air and other impurities in the furnace, thereby creating a vacuum environment for the subsequent sintering process. 50 The alloy green body will not react with oxygen, thus avoiding impurities and defects caused by oxidation; secondly, CuCr 50 The alloy green body is easy to volatilize at high temperature, and the vacuum environment can reduce the collision of gas molecules, thereby reducing volatilization, which helps to maintain CuCr 50 The integrity of the alloy green body is to avoid quality loss due to volatilization; thirdly, in a vacuum environment, CuCr 50 The gaps between particles in the alloy green body will be reduced, and the particles will be more closely bonded, which will help to increase the CuCr 50 The density and strength of the alloy green body are improved, while reducing the formation of gas pores, thereby increasing the CuCr 50 Density and durability of sintered alloy.
[0042] In addition, CuCr 50 The alloy green body is heated in a gradient manner, which can specifically include the following two stages. The first is the preheating stage, which specifically includes:
[0043] The first preheating stage: start heating at a slower heating rate (for example, 2-3°C / min), raise the temperature to a lower preheating temperature (300-400°C), and keep it at the preheating temperature for 1-2 hours.
[0044] Second preheating stage: After preheating and heat preservation, the preheating temperature is increased to the intermediate temperature (700-800°C) at a heating rate of 4-6°C / min, and is kept at the intermediate temperature for 0.5-1h.
[0045] After preheating, solid phase sintering is performed. Specifically, the intermediate temperature is raised to the sintering temperature (980-1070°C) at a heating rate of 6-8°C / min and kept at the intermediate temperature for 2-4 hours to sinter CuCr 50 The alloy green body is solid phase sintered.
[0046] Furthermore, after the sintering is completed, the CuCr 50 The alloy sintered body is cooled. Usually, when the temperature of the sintering furnace drops to 500°C, the cooling speed can be accelerated by a fan to shorten the sintering cycle and improve production efficiency.
[0047] In this embodiment, by adopting a gradient heating method, the speed of temperature change can be slowed down, which helps to evenly transfer heat, thereby reducing CuCr 50 The internal stress of the alloy green body caused by the sudden temperature change helps to prevent CuCr 50 In addition, preheating at a lower temperature can 50 The adsorbed gas on the surface of the alloy green body escapes, reducing the porosity, and the subsequent gradual heating helps CuCr 50 A finer and more uniform grain structure is formed inside the alloy green body, thereby increasing the CuCr 50 Density and mechanical properties of the alloy. On the contrary, if the CuCr 50 Sintering of the alloy green body may result in CuCr 50 A large temperature gradient is generated inside the alloy green body, which easily causes thermal stress concentration. The accumulation of internal stress will lead to the formation of microcracks or the expansion of existing pores, thus causing cracks or other defects. In addition, during the preparation process, since copper powder and chromium powder or conductive additives and strengthening phases contain adsorbed gas or moisture, if the direct rapid heating method is adopted, these gases do not have enough time to escape, but form bubbles at high temperature and are sealed in the CuCr 50 The inside of the alloy leads to the formation of pores, while the gradient heating provides more opportunities for these gases to escape by gradually heating, reducing the formation of pores.
[0048] It should be noted that in this embodiment, the CuCr 50 During the sintering process of the alloy green body, a sintering aid may be added, such as molybdenum silicide (MoSi2).
[0049] S4: The CuCr 50 The alloy sintered body is placed in a hot isostatic pressing device at a temperature of 920°C for hot isostatic pressing to obtain CuCr 50 The alloy is subjected to hot isostatic pressing, wherein the pressure is set to 110 MPa and the holding time is set to 3 h.
[0050] In another exemplary embodiment, the present application also provides a CuCr 50 A method for preparing an alloy, comprising:
[0051] S10: Copper powder, chromium powder, graphite and titanium carbide (TiC) were mixed in a ratio of 49.98%, 49.8%, 0.02% and 0.2% and ball-milled in a ball mill mixing tank for 9 hours at a ball-to-material ratio of 1:1.1 to obtain CuCr 50 alloy powder;
[0052] S20: The CuCr 50 The alloy powder is placed in a mold coated with a release agent, and the CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 Alloy green billet, wherein the press pressure is set to 11 MPa, the holding time is set to 0.2 s, and the press pressure relief time is set to 1.5 s;
[0053] S30: The CuCr 50 The alloy green body is placed in a vacuum sintering furnace and sintered by gradient heating to obtain CuCr 50 Alloy sintered body;
[0054] Different from the previous embodiment, titanium boride (TiB2) can be added as a sintering aid in this step.
[0055] S40: The CuCr 50 The alloy sintered body is placed in a hot isostatic pressing device at a temperature of 940°C for hot isostatic pressing to obtain CuCr 50 Alloy, wherein the hot isostatic pressing pressure is set to 120 MPa, and the heat preservation and pressure holding time is set to 4 h.
[0056] In another exemplary embodiment, the present application also provides a CuCr 50 A method for preparing an alloy, comprising:
[0057] S100: Copper powder, chromium powder, carbon fiber and alumina (Al2O3) were mixed in a ratio of 49.47%, 49.8%, 0.03% and 0.7% and ball milled in a ball mill mixing tank for 10 hours with a ball-to-material ratio of 1:1.2 to obtain CuCr 50 alloy powder;
[0058] S200: The CuCr 50 The alloy powder is placed in a mold coated with a release agent, and the CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 Alloy green billet, wherein the press pressure is set to 12 MPa, the holding time is set to 0.3 s, and the press pressure relief time is set to 2 s;
[0059] S300: The CuCr 50 The alloy green body is placed in a vacuum sintering furnace and sintered by gradient heating to obtain CuCr 50 Alloy sintered body;
[0060] Different from the previous embodiment, nickel silicide (NiSi) can be added as a sintering aid in this step.
[0061] S400: The CuCr 50 The alloy sintered body is placed in a hot isostatic pressing device at a temperature of 960°C for hot isostatic pressing to obtain CuCr 50 Alloy, wherein the hot isostatic pressing pressure is set to 130 MPa, and the holding time is set to 5 h.
[0062] In another exemplary embodiment, the present application also provides a CuCr 50 A method for preparing an alloy, comprising:
[0063] S1000: Copper powder, chromium powder, carbon nanotubes and zirconium oxide were mixed in a ratio of 49.97%, 49.7%, 0.03% and 0.3% and ball milled in a ball mill mixing tank for 12 hours with a ball-to-material ratio of 1:1.3 to obtain CuCr 50 alloy powder;
[0064] S2000: The CuCr 50 The alloy powder is placed in a mold coated with a release agent, and the CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 Alloy green billet, wherein the press pressure is set to 12 MPa, the holding time is set to 0.3 s, and the press pressure relief time is set to 2 s;
[0065] S3000: The CuCr 50 The alloy green body is placed in a vacuum sintering furnace and sintered by gradient heating to obtain CuCr 50 Alloy sintered body;
[0066] Different from the previous embodiment, zirconium boride (ZrB2) can be added as a sintering aid in this step.
[0067] S4000: The CuCr 50 The alloy sintered body is placed in a hot isostatic pressing device at a temperature of 980°C for hot isostatic pressing to obtain CuCr 50 Alloy, wherein the hot isostatic pressing pressure is set to 140 MPa, and the holding time is set to 6 h.
[0068] In the above embodiment, when preparing CuCr 50 In the process of alloying materials, carbon black, graphite, carbon fiber and carbon nanotubes are all used as conductive additives. By adding conductive additives, CuCr 50 A continuous conductive network is formed inside the alloy material, which increases the transmission channel of electrons and thus improves the CuCr 50 In addition to improving the conductivity, the conductive additive can also enhance the conductivity of CuCr50 The mechanical properties of the alloy are due to the conductive additive particles being able to fill the CuCr 50 The gaps between alloy particles reduce porosity and increase CuCr 50 The density of the alloy, and the increase in density can make CuCr 50 The particles inside the alloy material are more closely bonded, thereby increasing the CuCr 50 The hardness of the alloy. Further, after adding conductive additives, CuCr 50 The microstructure of the alloy will change, and the conductive additive particles will be evenly distributed in the CuCr 50 In the alloy matrix, fine dispersed strengthening phases are formed, which can hinder the expansion of cracks and thus improve the CuCr 50 The toughness and fracture resistance of the alloy.
[0069] Below, under the same process conditions, the present application uses the following data to illustrate the effects of not adding a conductive additive and adding a conductive additive on CuCr 50 The influence of various properties of the alloy is shown in Table 1:
[0070] Table 1
[0071] Performance Indicators No conductive additives added Add conductive additives Hardness (HB) 75~80 90.0~95.0 Toughness (J) 20~30 30~40 Fracture resistance (MPa·m^1 / 2) 15~20 20~25 <![CDATA[Measured density (g / cm 3 )]]> 7.30~7.50 7.64~7.97 Density(%) 92~94% 96~98%
[0072] As shown in Table 1, when no conductive additive is added, CuCr 50 The hardness of the alloy is 75-80HB. After adding conductive additives, CuCr 50 The hardness of the alloy is significantly increased to 92.4-103.9HB, which indicates that the addition of conductive additives makes CuCr 50 The mechanical strength of the alloy is enhanced. Without adding conductive additives, CuCr 50 The toughness of the alloy is low, and the impact absorption energy is about 20 to 30J. After adding conductive additives, CuCr 50 The toughness of the alloy has been improved, and the impact absorption energy has increased to 30-40J, which means that CuCr 50 The alloy is better able to resist impact loads without breaking. Without the addition of conductive additives, CuCr 50 The alloy has a weak fracture resistance, with a fracture toughness value of about 15-20 MPa·m^1 / 2. After adding conductive additives, CuCr 50 The alloy's fracture resistance is enhanced, and the fracture toughness value is increased to 20-25MPa·m^1 / 2, which indicates that CuCr 50 The alloy has better resistance to stress concentration or crack propagation. Without adding conductive additives, CuCr 50 The measured density of the alloy is 7.3-7.5 g / cm 3, after adding conductive additives, CuCr 50 The measured density of the alloy was significantly increased to 7.64-7.97 g / cm 3 , which reflects the CuCr 50 The internal pores of the alloy are reduced and the structure is more compact. Without adding conductive additives, CuCr 50 The density of the alloy is relatively low, ranging from 92% to 94%. After adding conductive additives, CuCr 50 The density of the alloy is significantly improved to 95.86-99.99%, close to the theoretical fully dense state, which means that CuCr 50 There are virtually no voids within the alloy, which improves its overall performance.
[0073] Furthermore, the present invention also adds carbon black, graphite, carbon nanotubes and carbon fibers and other conductive additives to prepare CuCr 50 The properties of the alloy were tested and the test results are shown in Table 2:
[0074] Table 2
[0075]
[0076] In Table 2, CuCr prepared using carbon black as a conductive additive 50 The alloy performs best in terms of hardness, toughness, fracture resistance, measured density and compactness. Therefore, this application uses carbon black as the 50 The best conductive additive for alloys.
[0077] In addition, it should be noted that the reason why the proportion of the conductive additive is set to be in the range of 0.01-0.03% is that within this range, conductive additives including carbon black, graphite, carbon nanotubes and carbon fibers can be 50 An effective conductive network is formed inside the alloy, which increases the transmission path of electrons and thus improves the CuCr 50 At the same time, these additives can also fill the gaps between alloy particles, reduce porosity, increase density, and further improve the hardness, toughness and fracture resistance of the alloy.
[0078] If the proportion of the conductive additive is less than 0.01%, the conductive network formed is not enough to effectively improve the CuCr 50 The conductivity of the alloy and the effect of enhancing the mechanical properties of the alloy will also be weakened, because the amount of additives is not enough to effectively fill the gaps between the alloy particles. This will result in CuCr 50 The mechanical properties of the alloy, such as hardness, toughness and fracture resistance, have not been significantly improved, and the density cannot be significantly improved.
[0079] On the contrary, if the proportion of the conductive additive is greater than 0.03%, it will cause CuCr 50 Too much additives in the alloy will affect CuCr 50 The overall properties of the alloy. Too much additives will interfere with the CuCr 50 The microstructure of the alloy may cause unnecessary defects, such as the formation of agglomerates or affect the uniformity of the alloy matrix, which may weaken the CuCr 50 The alloy's hardness, toughness and fracture resistance. In addition, too much conductive additive will also cause CuCr 50 The alloy is difficult to process. For example, too much conductive additive will cause CuCr 50 Uneven shrinkage or other adverse reactions of the alloy.
[0080] On the basis of the above embodiments, in other embodiments, in addition to tungsten carbide (WC), titanium carbide (TiC), aluminum oxide (Al2O3) and zirconium oxide (ZrO2), the present application also uses chromium carbide (Cr3C2) and vanadium carbide (VC) and yttrium oxide (Y2O3) as strengthening phases for CuCr 50 Preparation of alloy. In this application, by adding strengthening phase, high hardness, wear resistance and thermal stability of small particles can be introduced to optimize CuCr 50 The microstructure of the alloy, these particles can fill the CuCr 50 The pores in the alloy matrix reduce defects and thus increase the CuCr 50 The hardness, toughness and density of the alloy are improved. Specifically, on the one hand, the strengthening phase particles (such as carbides or oxides) are uniformly distributed in the CuCr 50 In the alloy matrix, a small and dispersed second phase can be formed. These strengthening phase particles can hinder the CuCr 50 Dislocation movement of metal atoms in the alloy matrix (dislocation is a linear defect in the crystal structure. When external force acts on CuCr 50 When alloying, dislocations will slip within the lattice, resulting in CuCr 50 alloy deformation), thereby increasing the CuCr 50 The hardness of the alloy, this dispersion strengthening mechanism makes CuCr 50 The alloy is difficult to deform when subjected to external forces. On the other hand, since the strengthening phase particles usually have higher hardness and wear resistance, their presence can enhance the CuCr 50 The alloy surface resistance to wear, when CuCr 50 These hard particles can protect the CuCr when the alloy is subjected to friction or impact. 50 The alloy matrix is protected from damage.
[0081] Next, based on Table 1, this application uses Table 3 to prepare CuCr with and without adding a strengthening phase. 50 The properties of the alloys are compared and explained:
[0082] Table 3
[0083] Performance Indicators No reinforcement phase added Add strengthening phase Hardness (HB) 90.0~95.0 95.0~99.0 Toughness (J) 30~40 40~45 Fracture resistance (MPa·m^1 / 2) 20~25 25~30 <![CDATA[Measured density (g / cm 3 )]]> 7.60~7.80 7.80~8.0 Density(%) 96~98% 98~99.5%
[0084] It can be seen from Table 3 that compared with the CuCr prepared without adding the strengthening phase, the 50 The hardness, toughness, fracture resistance, density and compactness of the alloy are significantly improved. Among them, high hardness helps to enhance the CuCr 50 The alloy's ability to resist plastic deformation makes it more durable; high toughness helps improve CuCr 50 The alloy's ability to withstand impact loads, reducing the risk of fracture due to sudden stress; the higher the fracture resistance value, the better the CuCr 50 The alloy can more effectively prevent the development of cracks, thereby improving its service life and safety; the measured density is from 7.6 to 7.8 g / cm 3 Increased to 7.8~8.0g / cm 3 , the increase in density is usually accompanied by a decrease in porosity, which means that CuCr 50 The alloy is more compact and has fewer structural defects, which helps to improve conductivity and mechanical strength; the density increases from 96-98% to 98-99.5%, indicating that the CuCr prepared by adding the strengthening phase 50 The alloy has achieved a state close to the theoretically fully dense state, almost eliminating pores and other microscopic defects within the material, which is essential for ensuring good electrical conductivity and enhancing mechanical properties;
[0085] Based on Table 3, the present application has selected tungsten carbide (WC) as the optimal strengthening phase through experiments. The reason is that tungsten carbide (WC) has a very high hardness compared to other strengthening phase materials such as chromium carbide (Cr3C2) and oxides. This high hardness helps to significantly improve the CuCr 50 In addition, tungsten carbide (WC) can remain stable at high temperatures and is not prone to softening or melting, which is very important for CuCr alloys that need to withstand high temperatures and arcs. 50 Alloy contacts are very important because good thermal stability can prevent CuCr 50 The alloy contacts were damaged due to overheating.
[0086] Next, based on Table 3, this application uses Table 4 to analyze the CuCr prepared by the various strengthening phases involved above. 50 The properties of the alloys are compared and explained:
[0087] Table 4
[0088]
[0089] As can be seen from Table 4, CuCr prepared based on tungsten carbide (WC) 50 The alloy has the highest hardness, reaching 95.0~100.0HB. CuCr prepared based on other strengthening phases such as titanium carbide (TiC) and zirconium oxide (ZrO2) 50 The alloy also exhibits high hardness, but slightly lower than tungsten carbide. CuCr based on tungsten carbide (WC) 50 The alloy also has the highest toughness range, which is 40-45 J. CuCr based on tungsten carbide (WC) 50 The alloy has the highest fracture resistance, which is 25-30MPa·m^1 / 2, showing that tungsten carbide (WC) is very effective in preventing CuCr 50 The effectiveness of crack propagation in alloys based on CuCr prepared with other strengthening phases 50 Although the alloy's fracture resistance has also improved, it is not as good as tungsten carbide. All strengthening phase materials lead to CuCr 50 The increase in density of the alloys, with WC providing the highest density range, reflects a more compact structure. CuCr based on WC 50 The alloy has achieved the highest density, based on CuCr prepared by other strengthening phases 50 The density of the alloy is also higher, but slightly lower than tungsten carbide.
[0090] It should be noted that in the above embodiments, the ratio of the strengthening phase is controlled to be 0.2-0.7% because: within this ratio range, the strengthening phase particles (such as carbides or oxides) can be evenly distributed in the CuCr 50 In the alloy matrix, a small and dispersed second phase is formed, which hinders the CuCr 50 The dislocation movement of metal atoms in the alloy matrix increases the hardness of the alloy. At the same time, the presence of strengthening phase particles enhances the CuCr 50 The ability of the alloy surface to resist wear and protect the substrate from damage.
[0091] If the proportion of the strengthening phase is less than 0.2%, it is verified by experiments that insufficient dispersion strengthening phase can be formed, resulting in the CuCr 50 The improvement of alloy performance is not obvious, and the improvement of alloy hardness, toughness, density and other aspects is limited. If the proportion of strengthening phase is higher than 0.7%, too many strengthening phase particles may be introduced, which will not only increase production costs, but also lead to CuCr 50 A large number of aggregated particles appear inside the alloy, which affects the CuCr 50The uniformity and mechanical properties of the alloy may even lead to problems such as increased brittleness. Therefore, in order to obtain the best performance improvement effect, the present application strictly controls the proportion of the strengthening phase within the range of 0.2-0.7%.
[0092] In other embodiments, in addition to molybdenum silicide (MoSi2), titanium boride (TiB2), nickel silicide (NiSi) and zirconium boride (ZrB2), the present application also uses iron silicide (FeSi), cobalt silicide (CoSi), titanium silicide (TiSi2), zirconium silicide (ZrSi2) and tungsten silicide (WSi2) as sintering aids. 50 During the solid phase sintering of the alloy green body, adding sintering aids can bring the following technical effects: 1. Sintering aids can reduce CuCr 50 The temperature required for the alloy green body to reach densification can not only reduce energy consumption, but also reduce the requirements for equipment, thereby reducing production costs; 2. The sintering aid can fill CuCr 50 The gaps between alloy powder particles reduce porosity and increase CuCr 50 The high density of the alloy means fewer pores and defects, which helps to improve the CuCr 50 Mechanical properties and conductivity of the alloy; 3. Sintering aids can affect CuCr 50 The microstructure of the alloy forms more uniform and fine grains, which helps to increase the CuCr 50 The strength and toughness of the alloy; 4. Sintering aids can form second phase particles or improve CuCr 50 The bonding strength of the alloy matrix is enhanced by CuCr 50 The hardness, wear resistance and compressive strength of the alloy. In summary, by adding sintering aids, the CuCr 50 The sintering process and final properties of the alloy make it more suitable for application environments with high pressure, high temperature and frequent operations.
[0093] Among the sintering aids listed above, after experiments, this application selects molybdenum silicide (MoSi2) or titanium boride (TiB2) as the best sintering aids. Among them, molybdenum silicide (MoSi2) has a very high melting point (about 2030°C) and good oxidation resistance, and can maintain CuCr at high temperatures. 50 The integrity of the alloy structure makes CuCr 50 The alloy is not easy to melt or soften; in addition, under high temperature environment, a dense silicon dioxide protective layer will form on the surface of molybdenum silicide (MoSi2), which can effectively prevent oxygen and other corrosive gases from attacking CuCr 50 Further oxidation inside the alloy can increase the CuCr 50The heat resistance of the alloy; further, molybdenum silicide (MoSi2) can form a liquid phase during the sintering process, promoting the CuCr 50 Diffusion and rearrangement between alloy powder particles, thereby increasing CuCr 50 Density of the alloy.
[0094] Titanium boride (TiB2) has an extremely high hardness (about 32GPa) and can significantly increase the CuCr 50 The alloy has good wear resistance and compressive strength; in addition, due to the low thermal expansion coefficient of titanium boride (TiB2) and CuCr 50 The thermal expansion coefficient of the alloy matrix is well matched, which can reduce the CuCr under rapid temperature changes. 50 The stress concentration inside the alloy increases the CuCr 50 Thermal shock resistance of alloys.
[0095] Below, the present invention uses CuCr prepared without adding sintering aid and with adding sintering aid 50 The various properties of the alloys are compared and explained, as shown in Table 5:
[0096] Table 5
[0097]
[0098] In Table 5, compared with the CuCr prepared without adding sintering aid, the CuCr 50 The alloy has further improved in various performance indicators. Among them, the sintering aid can form uniform and fine grains, thereby improving the CuCr 50 The hardness of the alloy; sintering aids help improve CuCr 50 The microstructure of the alloy reduces internal defects, thereby increasing the CuCr 50 The toughness and impact resistance of the alloy; sintering aids are optimized by CuCr 50 Alloy matrix bonding and reducing internal defects make CuCr 50 The alloy has better resistance to stress concentration or crack propagation; the measured density is further increased to 7.9-8.1 g / cm 3 , sintering aids promote CuCr 50 Diffusion and rearrangement between alloy particles reduce porosity, thereby increasing CuCr 50 The measured density of the alloy is significantly increased to 99-99.8%, close to the theoretical fully dense state, which means that CuCr 50 There is almost no void inside the alloy, which greatly improves the CuCr 50 Electrical conductivity and mechanical strength of the alloy.
[0099] In the above embodiment, the present application tests multiple pressure values, including those below 9.5 MPa and above 12 MPa. By observing the CuCr 50 The deformation and cracking of the alloy green body and the quality of the sintered product were studied. It was found that 9.5-12 MPa was an ideal pressure range. Under this pressure, the initial pressed CuCr 50 The density of the alloy green body can reach 92-94%. On the one hand, this density is sufficient to support the CuCr 50 The alloy green body will not deform during the subsequent processing and sintering process, thus ensuring the dimensional accuracy and shape stability of the product; on the other hand, the CuCr 50 The alloy green body has a moderate internal pore structure, which is conducive to more thorough gas discharge during the subsequent vacuum sintering process, thereby reducing defects inside the material and improving the performance of the final product. In addition, the density also helps CuCr 50 The alloy green body forms a uniform and dense microstructure during the sintering process, which can improve the electrical conductivity and resistance to fusion welding of the material.
[0100] At the same time, the present application also found through testing that if the press pressure is greater than 12Mpa, it will cause CuCr 50 Over-compaction of the alloy green body will result in a density exceeding 94% or even higher. Over-compaction will increase the CuCr 50 The stress inside the alloy green body will cause the CuCr 50 The internal microstructure of the alloy green body will change during the subsequent sintering process, such as microcracks or deformation. 50 The alloy green body is not easy to exhaust during the subsequent sintering process, resulting in pores or inclusions in the sintered material. The presence of pores and inclusions will reduce the conductivity and resistance to welding of the material, resulting in a decrease in the performance of the vacuum circuit breaker capacitor bank, and may even cause equipment failure during operation. In addition, if the press pressure is less than 9.5Mpa, it will cause CuCr 50 The density of the alloy green body is insufficient, that is, the density is less than 92%, and insufficient density will lead to CuCr 50 The strength and hardness of the alloy green body are not enough to resist the external force during the demolding process, and it is easy to deform or crack during the demolding process, thereby reducing the yield and quality of the product.
[0101] In summary, in order to obtain high-quality CuCr 50 Alloy contacts should be strictly controlled in the pre-pressing process within the range of 9.5 to 12 MPa to ensure that CuCr 50 The density of the alloy green body is in the range of 92-94%, thereby avoiding the above-mentioned quality problems caused by improper pressure.
[0102] In the above embodiment, the holding time of the press is set to 0.1 to 0.3 s. 50 The results are based on our in-depth understanding and practical experience of the alloy powder pressing process. Within this holding time range, the press can give CuCr 50 The alloy powder is kept under pressure for a sufficient time so that it can fully adapt to the shape of the mold and reach a stable molding state. In addition, within this holding time range, the CuCr 50 The bonding between the alloy powder particles can reach an ideal state, making CuCr 50 The density of the alloy green body can be maintained between 92% and 94%. At the same time, the present application has found through experiments that if the holding time is too short (less than 0.1s), the CuCr 50 The alloy powder cannot fully adapt to the shape of the mold, resulting in the CuCr 50 The internal stress distribution of the alloy green body is uneven, which leads to the CuCr 50 The density of the alloy green body is insufficient, which will cause quality problems such as deformation and cracking of the product, reducing the yield rate. On the contrary, if the holding time is too long (greater than 0.3s), it can cause excessive wear of the mold and press parts, thereby increasing maintenance costs.
[0103] In summary, setting the holding time of the press within the range of 0.1 to 0.3 s has been experimentally verified. Within this time range, the CuCr 50 The density of the alloy green body reaches the ideal range (92% to 94%), thus ensuring the product quality.
[0104] In the above embodiment, the pressure relief time of the press is controlled within the range of 1 to 2 seconds. 50 The results are based on the in-depth understanding and practical experience of the alloy powder pressing process. Within this pressure relief time range, the CuCr 50 The alloy green body can gradually release the internal stress under the effect of elastic aftereffect without excessive expansion or deformation, which helps to maintain the CuCr 50 The integrity and shape accuracy of the alloy green body provide a good foundation for subsequent processing and sintering. It has been found through experiments that if the pressure relief time is less than 1s, the CuCr 50 The stress inside the alloy green body is difficult to be fully released, which will cause deformation or cracking during subsequent processing or sintering. In addition, too fast pressure relief speed will also cause the CuCr 50The surface of the alloy green billet will crack or peel off, thus reducing the product quality. If the pressure relief time is greater than 2s, it will cause excessive wear of the mold and press parts, thereby increasing maintenance costs.
[0105] In summary, it has been experimentally verified that the pressure relief time of the press is controlled within the range of 1 to 2 seconds, which is a relatively reasonable time range. This pressure relief time not only ensures that CuCr 50 The integrity and shape accuracy of the alloy green body also reduces maintenance costs.
[0106] In the above embodiment, the CuCr 50 Solid phase sintering of alloy green body is mainly based on the following factors:
[0107] In the first preheating stage: at a relatively low temperature (300-400°C), the adsorbed gas and moisture in the CuCr50 alloy powder can be effectively removed. If these gases and moisture cannot escape in time, they will form holes or bubbles during the subsequent high-temperature sintering process, thereby reducing the density of the material. A relatively low initial heating rate (2-3°C / min) helps ensure uniform heating of the entire sample and reduce internal stress caused by temperature gradients.
[0108] In the second preheating stage (700-800℃): In this temperature range, elements such as Cu and Cr begin to diffuse to a certain extent, making the contact between powder particles closer. This step is very important for forming a preliminary bond. Although the melting point of copper is about 1085℃ and the melting point of chromium is about 1907℃, between 700 and 800℃, premature melting of alloy components can be avoided and the solid-state sintering process can be maintained.
[0109] Solid phase sintering stage (980~1070℃): This temperature range is close to but lower than the melting point of copper, which can make CuCr 50 The alloy powder reaches a high degree of densification. At this temperature, the bonding force between the powder particles is significantly enhanced, forming a denser structure. High temperature helps to further refine the grains and improve the mechanical properties of the material. At the same time, the appropriate holding time (2 to 4 hours) can ensure that the sintering process is fully completed and reduce internal defects.
[0110] It should be noted that the sintering temperature is set within the range of 980-1070°C, mainly based on the following considerations:
[0111] Aspect 1: The melting point of copper is about 1085℃, while the melting point of chromium is much higher, about 1907℃. In the temperature range of 980~1070℃, CuCr 50The alloy powder has not yet reached the melting point of copper, so premature melting of copper can be avoided, thereby maintaining the solid-state sintering process and allowing the alloy powder to achieve a higher density under solid conditions.
[0112] Aspect 2: Within this temperature range, elements such as copper and chromium begin to diffuse to a certain extent, making the contact between powder particles closer.
[0113] Aspect 3: Within this temperature range, the bonding force between powder particles is enhanced, and a denser structure can be formed.
[0114] In summary, by adopting gradient heating, CuCr 50 The alloy green body can be heated evenly during the sintering process, remove adsorbed gases, promote diffusion between particles, avoid premature melting, and make CuCr 50 The alloy achieves higher density and excellent microstructure.
[0115] In the above embodiment, the CuCr 50 The alloy sintered body is placed in a hot isostatic pressing device at a temperature of 920-980°C for hot isostatic pressing. This application is determined through experimental research and process optimization. It is found that in the temperature range of 920-980°C, CuCr 50 The grains of the alloy sintered body can further grow and rearrange, which helps to reduce the CuCr 50 The pores and defects inside the alloy sintered body are reduced, thereby improving the density. In addition, this temperature range is also beneficial to the CuCr 50 The atomic diffusion in the alloy sinter promotes the bonding between particles, thus forming a more uniform and compact microstructure. This application also tested multiple temperature points, including those below 920°C and above 980°C. The test found that if the temperature is less than 920°C, it will cause CuCr 50 Insufficient atomic diffusion in the alloy sintered body and insufficient bonding between particles will reduce the density of the product. In addition, it will also lead to CuCr 50 The pores inside the alloy sintered body cannot be completely closed, which will reduce the mechanical properties and density of the product. If the temperature is higher than 980℃, it will cause excessive grain growth, and the large grain size will weaken the CuCr 50 The mechanical properties of the alloy sintered body, including strength and toughness, are also affected. In addition, excessively high temperatures can also cause certain elements (such as chromium and copper) to evaporate or volatilize, resulting in CuCr 50 The alloy sintered body has segregation or other defects, which reduces the CuCr 50 Electrical conductivity and welding resistance of alloy sintered bodies.
[0116] Furthermore, after further experiments, this embodiment selects 950°C as the optimal temperature for hot isostatic pressing. After testing, it is found that at this temperature, the CuCr 50 The density and mechanical properties of the alloy, in addition, at this temperature, CuCr 50 The atomic activity inside the alloy is the most active, which is most conducive to the closure and elimination of pores and defects, and can maximize the CuCr 50 Overall properties of the alloy.
[0117] In the above embodiment, the hot isostatic pressing pressure range of 110-140 MPa is also obtained by the present application based on a series of experimental tests. It is found through experiments that within this pressure range, CuCr 50 The pores and defects inside the alloy sintered body can be effectively compressed and eliminated, which helps to improve the mechanical properties and electrical conductivity of the alloy material. 50 The grains in the alloy sintered body can rearrange and grow to form a more uniform and compact microstructure, which helps to improve the mechanical properties and resistance to welding of the alloy material. Tests have found that when the pressure is greater than 140Mpa, CuCr 50 The alloy material will undergo excessive plastic deformation due to excessive pressure, which will cause significant changes in the grain structure inside the material, thus affecting its mechanical properties and conductivity. When the pressure is less than 110Mpa, CuCr 50 The pores and defects inside the alloy sintered body cannot be fully compressed and eliminated, which will lead to CuCr 50 The grains inside the alloy material are unevenly arranged, forming an uneven microstructure, which will affect the CuCr 50 Mechanical properties and welding resistance of alloy materials.
[0118] In summary, in order to ensure CuCr 50 The alloy sintered body can obtain the best density, mechanical properties and conductivity during the hot isostatic pressing process. It is a reasonable choice to set the pressure within the range of 110 to 140 MPa.
[0119] Furthermore, after further experiments, this embodiment selects 125Mpa as the optimal pressure value for hot isostatic pressing. Under this pressure, CuCr 50 The alloy is fully densified, while avoiding excessive pressure that may cause CuCr 50 The grains inside the alloy are excessively deformed or new defects are generated. In addition, the pressure value of 125Mpa can also maximize the 50 The microstructure of the alloy is optimized to make CuCr 50The grains within the alloy are able to rearrange and grow, forming a more uniform and compact microstructure.
[0120] In the above embodiment, experimental detection shows that if the heat preservation and pressure holding time is greater than 6 hours, CuCr 50 The microstructure of the alloy sintered body changes, such as grain growth and phase transformation, which affects the CuCr 50 The mechanical properties and electrical conductivity of the alloy material. In addition, long-term high temperature and high pressure environment will accelerate the aging and wear of the equipment and shorten the service life of the equipment. If the heat preservation and pressure holding time is less than 3h, the CuCr 50 The pores and defects inside the alloy sintered body are fully compressed and eliminated, which will lead to the CuCr 50 The density of the alloy material is insufficient. In addition, the shorter insulation and pressure holding time will also lead to CuCr 50 The quality of the alloy material is unstable because the densification process inside the material may not be complete, which will affect the CuCr 50 Reliability and service life of alloy materials.
[0121] In summary, setting the hot isostatic pressing time to 3 to 6 hours can ensure the CuCr 50 The alloy sintered body obtains the best density, microstructure and mechanical properties during the hot isostatic pressing process.
[0122] It should be noted that in the prior art, cold isostatic pressing is often used to carry out CuCr 50 For alloy preparation, this application adopts hot isostatic pressing, which has the following advantages compared with cold isostatic pressing:
[0123] 1. During the hot isostatic pressing process, due to the high temperature, CuCr 50 The atoms and molecules inside the alloy can obtain more energy, making it easier for them to diffuse and migrate, which helps to form a more uniform and compact microstructure.
[0124] 2. During the hot isostatic pressing process, due to the combined effects of high temperature and high pressure, CuCr can be effectively compressed and eliminated. 50 The pores and defects inside the alloy make CuCr 50 The alloy is denser, which reduces the formation of resistance centers and thus improves conductivity.
[0125] 3. During hot isostatic pressing, CuCr 50 The alloy grains can further grow and rearrange to form a more uniform and dense microstructure, thereby enhancing the CuCr 50 The alloy's anti-welding and mechanical properties can meet the needs of high-performance application scenarios such as vacuum circuit breakers cutting capacitor banks.
[0126] 4. Cold isostatic pressing due to CuCr 50 The introduction of cold brittleness into the alloy will affect the CuCr 50 The mechanical properties and reliability of the alloy. Hot isostatic pressing can avoid this problem because the atomic activity at high temperature helps to reduce internal stress.
[0127] In addition, in another exemplary embodiment, the present application also provides a contact, the contact is used for a vacuum interrupter, the contact is based on the CuCr 50 Alloy preparation.
[0128] In this embodiment, the CuCr prepared by this method 50 The alloy is applied to vacuum interrupter contacts, which can bring the following functions and technical effects:
[0129] 1. CuCr prepared by this method 50 The alloy has good electrical conductivity and mechanical strength. Using it as a contact material can effectively improve the performance of the vacuum circuit breaker when cutting off the capacitor bank, especially its ability to break large currents has been enhanced. At the same time, it can also maintain good dielectric strength, ensuring the safe and stable operation of the power system.
[0130] 2. CuCr prepared by this method 50 The alloy has greatly improved its hardness, toughness, fracture resistance and density by optimizing the composition ratio and adopting advanced preparation processes, such as ball milling, pre-pressing, gradient temperature sintering and hot isostatic pressing. These performance improvements enable the contacts to better resist the occurrence of fusion welding when facing high-energy arcs, and reduce wear during frequent opening and closing operations.
[0131] 3. CuCr prepared by this method 50 The alloy has a greater air absorption effect and releases less gas than other materials. Therefore, in a vacuum environment, this alloy contact can provide better dynamic vacuum, which helps to reduce the impact of residual gas in the vacuum interrupter and thus improve the arc extinguishing efficiency of the circuit breaker.
[0132] 4. CuCr prepared by this method 50 The high hardness and density of the alloy enable it to maintain a good physical form when working in high pressure and high temperature environments, and it is not easy to deform or damage, thereby extending the service life of the contacts.
[0133] In summary, the CuCr prepared by this method 50 The application of alloys in vacuum interrupter contacts can not only improve the performance of vacuum circuit breakers, but also ensure the reliability and durability of contacts under extreme conditions, which has a positive impact on the safety and economy of power systems.
[0134] Figure 2 The CuCr with a size of 50 μm provided by an exemplary embodiment of the present application 50 Schematic diagram of the microstructure of the alloy after sintering; Figure 3 Another exemplary embodiment of the present invention provides a CuCr having a size of 100 μm. 50 Schematic diagram of the microstructure of the alloy after sintering. Figure 2 It can be seen that the CuCr prepared by this method 50 The chromium particles in the alloy are evenly distributed in the copper matrix, forming a relatively uniform and fine microstructure. This shows that the copper powder and the chromium powder are well mixed during the powder mixing stage and the subsequent pre-pressing process, and the bonding between the particles is further promoted by the sintering process. Figure 3 It also shows the uniform distribution of chromium particles in the copper matrix. Figure 2 In comparison, despite the increase in particle size, the chromium particles still maintain a relatively uniform dispersion state without obvious agglomeration. It should be noted that copper is an excellent conductor, while chromium improves the strength and wear resistance of the alloy. By maintaining the uniform distribution of chromium particles in the copper matrix and reducing the internal porosity (increasing density), a continuous and efficient electron transmission path can be formed, which helps to improve the CuCr 50 The overall electrical conductivity of the alloy, and good conductivity is essential to reduce energy losses, improve efficiency and ensure reliable current transmission.
[0135] Figure 4 The CuCr with a size of 50 μm provided by an exemplary embodiment of the present application 50 Schematic diagram of the microstructure morphology of the alloy after hot isostatic pressing; Figure 5 Another exemplary embodiment of the present invention provides a CuCr having a size of 100 μm. 50 Schematic diagram of the microstructure of the alloy after hot isostatic pressing. Figure 4 and Figure 5 It can be seen that the CuCr prepared by this method 50 Although the alloy has been treated with high temperature and high pressure, the morphology of the chromium particles has not changed significantly, and the chromium particles still maintain a relatively uniform distribution during sintering. This shows that the hot isostatic pressing process can not only further improve the density of the material, but also achieve this goal without destroying the original microstructure, thus ensuring the CuCr 50 The alloy has excellent comprehensive properties.
[0136] Figure 6 The CuCr with a size of 100 μm provided by an exemplary embodiment of the present application 50 Schematic diagram of the fracture microstructure of the alloy after hot isostatic pressing; Figure 7 Another exemplary embodiment of the present application provides a CuCr having a size of 200 μm. 50 Schematic diagram of the fracture structure morphology of the alloy after hot isostatic pressing. Figure 6 and Figure 7 It can be seen that the CuCr prepared by this method 50 After hot isostatic pressing, the cross section of the alloy shows extremely high density, and almost no pores or other types of defects are seen, indicating that the appropriate temperature, pressure and holding time used in this method are reasonable and can make CuCr 50 The alloy reaches a maximum density level close to the theoretical value (100% dense), which can make CuCr 50 The tensile strength, hardness and other mechanical properties of the alloy are significantly improved, making it less likely to deform or break when subjected to external forces; on the other hand, it can improve the CuCr 50 The conductive efficiency of the alloy is beneficial to reducing the resistance loss during the operation of the switchgear.
[0137] Figure 8 It is CuCr provided by an exemplary embodiment of the present application. 50 Schematic diagram of the macroscopic morphology of the alloy surface after laser treatment; Fig. 9 CuCr is provided by another exemplary embodiment of the present application. 50 Schematic diagram of the microstructure of the alloy surface after laser treatment. Figure 8 As shown), after laser remelting, CuCr 50 A new layer of smoother and finer texture is formed on the alloy surface; and from the microscopic point of view (such as Fig. 9 As shown), it can be seen that laser treatment makes CuCr 50 The chromium particles in the surface area of the alloy become smaller and more densely distributed, and these small, high-hardness chromium particles can hinder dislocation movement and significantly improve CuCr 50 In addition, the more closely packed chromium particles also help to form a continuous conductive network, thereby improving the CuCr 50 The electrical conductivity of the alloy. Furthermore, in applications such as vacuum circuit breakers, CuCr 50 The alloy contacts need to frequently cut off the current, and the high temperature generated during the process may cause the metal to melt and stick together (i.e., welding). 50 The uniform distribution of chromium particles in the alloy can increase the CuCr 50 The roughness of the alloy surface can improve the CuCr 50 The thermal stability of the alloy can reduce the CuCr 50 Risk of welding of alloys.
[0138] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A CuCr 50 The alloy preparation method is characterized in that: The preparation method comprises: Copper powder, chromium powder, conductive additive and reinforcing phase are prepared in a preset ratio and then ball milled to obtain CuCr 50 alloy powder; The CuCr 50 Alloy powder is pre-pressed to obtain CuCr 50 Alloy green body; For the CuCr 50 The alloy green body is solid phase sintered to obtain CuCr 50 Alloy sintered body; For the CuCr 50 The alloy sintered body is hot isostatically pressed to obtain CuCr 50 alloy.
2. The preparation method according to claim 1, characterized in that: The conductive additive includes any one of the following: carbon black, graphite, carbon nanotubes and carbon fibers.
3. The preparation method according to claim 1, characterized in that: The strengthening phase comprises carbide or oxide powder, wherein: The carbide includes any of the following: chromium carbide, tungsten carbide, titanium carbide and vanadium carbide; The oxide includes any one of the following: aluminum oxide, zirconium oxide and yttrium oxide.
4. The preparation method according to claim 1, characterized in that: The sintering aid comprises a boride or a silicide, wherein: The boride includes any of the following: titanium boride or zirconium boride; The silicide includes any one of the following: iron silicide, nickel silicide, cobalt silicide, molybdenum silicide, titanium silicide, zirconium silicide and tungsten silicide.
5. The preparation method according to claim 1, characterized in that: In the CuCr 50 During the pre-pressing process of the alloy powder, the pressure is set to 9.5-12 MPa.
6. The preparation method according to claim 1, characterized in that: In the CuCr 50 During the pre-pressing process of the alloy powder, the holding time is set to 0.1 to 0.3 s.
7. The preparation method according to claim 1, characterized in that: The CuCr 50 The alloy green body is solid phase sintered.
8. The preparation method according to claim 1, characterized in that: For the CuCr 50 The sintering temperature of the alloy green body for solid phase sintering is 980-1070°C.
9. The preparation method according to claim 1, characterized in that: The CuCr 50 The alloy sintered body is hot isostatically pressed at a temperature of 920 to 980°C.
10. The preparation method according to claim 1, characterized in that: The CuCr 50 The alloy sintered body is hot isostatically pressed at a pressure of 110 to 140 MPa.
11. The preparation method according to claim 1, characterized in that: For the CuCr 50 The holding time of hot isostatic pressing of the alloy sintered body is set to 3 to 6 hours.
12. A CuCr 50 The alloy is characterized in that The CuCr 50 The composition of the alloy and the mass percentage of each component are: Chromium powder: 49.6~49.8% Conductive additive: 0.01~0.03% Strengthening phase: 0.2~0.7% Copper powder: balance.
13. A contact, used in a vacuum interrupter, characterized in that: The contact is based on the CuCr according to claim 12 50 Alloy preparation.